2002
DOI: 10.2337/diacare.25.12.2123
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Combination Glipizide GITS/Metformin on Fibrinolytic and Metabolic Parameters in Poorly Controlled Type 2 Diabetic Subjects

Abstract: OBJECTIVE -Epidemiological studies have implicated increased plasminogen-activated inhibitor 1 (PAI-1) as a marker or predictor of accelerated coronary atherosclerotic disease in type 2 diabetes. We sought to determine whether metabolic control, independent of its oral mode of implementation, affects PAI-1 in patients with marked hyperglycemia.RESEARCH DESIGN AND METHODS -A total of 91 subjects were screened, subjected to a 4-week drug washout, and randomized to daily treatment with glipizide GITS (maximum 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 36 publications
1
23
0
3
Order By: Relevance
“…63 Treatment of hyperglycaemia with a sulphonylurea (SU) or metformin reduces PAI-1 levels, suggesting that glucose lowering, rather than the type of hypoglycaemic agent, modulates PAI-1 levels. 64 In addition to hyperglycaemia, hyperinsulinaemia also increases PAI-1 levels, 65 which explains elevated levels of this protein in insulin-resistant states. 66 Activity of tPA has been linked to diabetic complications.…”
Section: Coagulation Proteins Involved In Fibrinolysismentioning
confidence: 99%
“…63 Treatment of hyperglycaemia with a sulphonylurea (SU) or metformin reduces PAI-1 levels, suggesting that glucose lowering, rather than the type of hypoglycaemic agent, modulates PAI-1 levels. 64 In addition to hyperglycaemia, hyperinsulinaemia also increases PAI-1 levels, 65 which explains elevated levels of this protein in insulin-resistant states. 66 Activity of tPA has been linked to diabetic complications.…”
Section: Coagulation Proteins Involved In Fibrinolysismentioning
confidence: 99%
“…Other studies also demonstrated that metformin had benefical effects on Plasminogen Activator Inhibitor-1 (PAI-1), von Willebrand Factor (vWF) and fibrinogen. [12][13][14] Metformin was also shown to improve endothelial dysfuntion. 15,16 Rosiglitazone therapy was shown to reduce serum C reactive protein levels in type 2 diabetic patients.…”
Section: Introductionmentioning
confidence: 99%
“…Sulphonylureas are associated with a long-term failure rate of approximately 5 to 7% per year [9][10][11][12] and combination therapy is then needed to maintain treatment efficacy. Metformin, which acts primarily in the liver to reduce endogenous glucose production [13], in combination with sulphonylurea, is often a successful approach in poorly controlled type 2 diabetes [14][15][16][17].…”
mentioning
confidence: 99%